Co-Design visions of public makerspaces in China. Issue 3 (3rd July 2022) - Choi, Y.; Lam, B.; Chen, X.; de Sousa, S.; Liu, L.; Ni, M.
ABSTRACT: Enhancing creativity has become of vital importance in today's modern world as creativity plays an essential role in solving complex individual, business and social issues. This paper, therefore, considers how to develop a novel and inclusive means of fostering creative citizens in a bottom-up manner, especially in China, through co-design and public makerspaces. The paper discusses the notion of creativity and its relations with co-design and makerspace, critical requirements of co-design and makerspace design, and cultural differences in co-design. A literature review and a series of co-design workshops with Chinese and non-Chinese participants were applied. The research revealed that making activities should be more 'visible' and 'inclusive' to engage more and better with both makers and non-makers. This study also identified some differences between Chinese and non-Chinese groups in terms of space management and co-design approaches. The key findings would greatly value developing user-oriented makerspaces for creativity enhancement in China.